TREATMENT OUTCOMES OF CHILDHOOD TUBERCULOSIS WITH DOTS STRATEGY IN KOTTAYAM, KERALA. - Hanumantappa, Ramesh; Shoba, A; Manjula, V D (Indian Journal of Community Health, 2012)
Background: Childhood tuberculosis is a reflection of sputum-positive pulmonary tuberculosis and extent of transmission of tuberculosis in the community. Children suffer from serious form of tuberculosis and are more likely to die if not treated at proper time. Paediatricians are reluctant to refer them to Directly Observed Treatment- Short course (DOTS) centres. Present study is conducted to know the clinical profile and treatment outcomes of childhood tuberculosis patients registered under Revised National Tuberculosis Control Program (RNTCP) in Kottayam, Kerala. Methods: It was a record based cross-sectional study. Data was collected from RNTCP records from January to December 2009. Data was analysed using SPSS 16.0 and results were presented as proportions with 95% confidence limits. Chi-square test was used to find out the association. Results: The total number of paediatric tuberculosis cases was 155. There were 84 (55.6%) males and 67(44.4%) females. 66 (43.7%) were less than 5 years of age. Out of 117 (77.5%) pulmonary tuberculosis cases, 8 (0.06%) were sputum smear-positive. Among extra-pulmonary TB cases, peripheral lymph node disease [25 (73.5%)] was most common. The treatment completion rate was 90.7% with cure rate of 100% among sputum smear positive cases. Chi-square test showed significant association between age and treatment outcome (p-value <0.0001). Conclusions: Study showed that the RNTCP-DOTS is still the most effective strategy in treating childhood tuberculosis patients. Further studies are needed to assess the reasons for low proportion of smear positive and low TB meningitis cases.